The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1002/cne.902610207
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of mouse cerebellar circuits following methylazoxymethanol treatment during development: Immunohistochemistry of GABAergic elements and electron microscopic study

Abstract: Methylazoxymethanol (MAM) injected postnatally affects cerebellar development in mice. A single injection at the fifth postnatal day produces hypogranular cerebella whereas a single injection at birth produces, in addition, a disorderly cytoarchitecture of the folium and alteration of Purkinje cell positioning (Bejar et al.: Exp. Brain Res. 57:279-285, '85). In the present study we have used immunohistochemistry with anti-GABA immune serum and electron microscopy to further characterize these alterations. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…In our case one might suggest that, if this modulatory role is not impaired, the structure would persist because it remains functional. The situation is different in MAMo animals, since we already observed a great disorder of the cytoachitecture of the folium (Bkjar et al, 1985;de Barry et al, 1987): the PCs were scattered throughout the folium and no basket around the PC cell hillock was observed despite the presence of neurofilament-rich profiles near the PC soma. Our present observations complete these previous studies by confirming the malpositioning of PCs and disorientation of their dendrites; they also clearly indicate that basket cell axons, hence cell bodies, are present.…”
Section: Immunohistochemistry Of Nf-hmentioning
confidence: 82%
See 2 more Smart Citations
“…In our case one might suggest that, if this modulatory role is not impaired, the structure would persist because it remains functional. The situation is different in MAMo animals, since we already observed a great disorder of the cytoachitecture of the folium (Bkjar et al, 1985;de Barry et al, 1987): the PCs were scattered throughout the folium and no basket around the PC cell hillock was observed despite the presence of neurofilament-rich profiles near the PC soma. Our present observations complete these previous studies by confirming the malpositioning of PCs and disorientation of their dendrites; they also clearly indicate that basket cell axons, hence cell bodies, are present.…”
Section: Immunohistochemistry Of Nf-hmentioning
confidence: 82%
“…A single injection on the day of birth (MAMo animals) produces hypogranularity and a general disruption of the cytoarchitecture of the cerebellar folium (Jones et al, 1972;Bejar et al, 1985), while an injection at the fifth postnatal day (MAM5 animals) also produces hypogranularity , but the folium cytoarchitecture is preserved (Bejar et al, 1985). In a previous study (de Barry et al, 1987) we observed that the pericellular basket around the Purkinje cell (PC) body is absent in MAMo animals but still present in MAM5 animals. We did not, however, determine if the absence of the pericellular basket was due to the absence of basket cells or to the difficulty of basket cell axons reaching malpositioned PC bodies.…”
Section: Ini'roductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[12][13][14] The period of granule cell neurogenesis coincides with critical sensitivity to the environment. 15,16 Due to the unique characteristics of proliferation of GNPs postnatally, CTX may have strong toxicity on the developing cerebellum in children. Up to now, however, whether and how CTX affects progenitor cell proliferation and differentiation during the cerebellar development have not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the time of MAM administration, a different number of granule cells is eliminated with a proportional loss of parallel fibers. The hypogranular cerebellum, resulting from a single injection of MAM at birth (MAM 0 ), exhibits extensive cytoarchitectural disorder, altered nerve circuitry associated with cell malpositioning and ectopia, and absence of lamination similar to what occurs in granule cell-deficient mutants and to rodents treated at early postnatal ages with X-ray, virus, or antimitotic compounds (de Barry et al, 1987;Chen and Hillman, 1988;Hillman et al, 1988;de Barry and Gombos, 1989). The altered morphology is associated with neurotransmitter/receptor alterations (Johnston and Coyle, 1980;Olson et al, 1987;Bacon et al, 1989;Makowiec et al, 1991).…”
Section: Introductionmentioning
confidence: 99%